A Message from Daniel Stiffler, ATE-K President (The Advocate, 2019)
Dr. Dan Stiffler, ATE-K President, invites you to attend these upcoming state Conferences: November 8, 2019: KACTE/ATE-K Conference at Fort Hays State University April 3, 2019: ATE-K/ KACTE Conference at Baker University